Atypical celiac disease in a patient with type 1 diabetes mellitus and Hashimoto's thyreoiditis Atypische Sprue bei einem Patienten mit Diabetes mellitus Typ 1 und Hashimoto-Thyreoiditis - Schreiber, F. S.; Ziob, T.; Vieth, M.; Elsbernd, H. (Deutsche Medizinische Wochenschrift, 2011)
History and admission findings: A 49-year-old man presented with a four-week history of fatigue and physical weakness. He was of slender build (BMI 19,5 kg/m2) and pale. He also had vitiligo. Diabetes mellitus type 1 and Hashimoto thyreoiditis had been previously diagnosed. Investigations: Laboratory tests revealed iron deficiency anemia with depleted iron reserves (hemoglobin 5,9 g/dl; normal range 14,0 - 18,0). Vitamin Band folic acid were also low. A probable cause was thought to be malabsorption. Antibodies against endomysium and tissue transglutaminase were elevated. Esophagogastroduodenoscopy and videocapsule endoscopy showed villous atrophy in the duodenum and jejunum. Histomorphological findings were compatible with celiac disease (Marsh stage 3a). Osteodensitometry showed significantly lowered bone density. Diagnosis, treatment and course: These investigations indicated atypical celiac disease with malabsorption, anemia and osteoporosis. The patient received nutritional counseling and was put on a gluten-free diet. Supplementary iron, folic acid and vitamin Bwere prescribed. A bloodtransfusion was given for the symptomatic anemia. The osteoporosis was treated with calcium and vitamin D3. A follow-up examination after four months revealed complete remission of the abnormal clinical and laboratory findings with partial remission of endoscopic and histologic changes (reduced to Marsh stage 2). Conclusion: Because of the lack of gastrointestinal symptoms, the diagnosis of atypical celiac disease is often made only at an advanced stage and advanced age. The disease is often associated with other autoimmune disorders. © Georg Thieme Verlag KG Stuttgart - New York.
CRIS-Team Scopus Importer:2025-03-05
Keywords: anemia; atypical celiac disease; diabetes mellitus type 1; Hashimoto thyreoiditis; malabsorption; osteoporosis